Realizing the right to decent life as a basis social police of Belgium - Tyshchenko, O. (Київський національний університет імені Тараса Шевченка, 2017)
The article examines the peculiarities of the Belgian social security of the population as one of the European Union member. Current trends in the labor market in the part of effective regulation of employment are analyzed. The reform of the pension system, the practical provision of social benefits, including benefits for families with children is studied also. The innovative approaches, which are implemented in social support for people with disabilities is studie

У статті досліджуються особливості здійснення соціального забезпечення населення Бельгії як однієї з країн Європейського Союзу. Аналізуються сучасні тенденції функціонування ринку праці в частині  ефективного регулювання працевлаштування. Вивчається реформування системи пенсійного забезпечення, практичне забезпечення надання соціальних допомог, зокрема допомог сім’ям з дітьми. Розглядаються інноваційні підходи, які запроваджуються у сфері соціальної підтримки осіб з обмеженими можливостями
РЕАЛІЗАЦІЯ ПРАВА НА ГІДНЕ ЖИТТЯ ЯК ОСНОВА СОЦІАЛЬНОЇ ПОЛІТИКИ БЕЛЬГІЇ
Keywords: Belgium; social policy; decent life; social provision; social assistance; health care; Бельгія; соціальна політика; гідне життя; соціальне забезпечення; соціальні допомоги; охорона здоров’я